Pathomorphological effects in pigs following cadmium chloride parentral administration - Singh, R; Singh, K P; Parihar, N S (The Indian Journal of Animal Sciences, 2012)
The cadmium chloride injections caused swelling of the scrotum and periorchitis after intra-epididymal and subcutaneous (thigh region) inoculations resulting in adhesions between the testes and scrotal walls restricting the movements of the testicles. The testes were small in size. In the intra-epididymally. inoculated pigs there was distinct testicular discoloration and occurrence of dark yellow foci underneath the tunica albuginea near the site of inoculations. The epididymis also revealed local swelling, oedema, haemorrhages and necrosis. The degenerative changes in the testicles were most severe following intra-epididymal inoculation and least severe following subcutaneous injection in the neck. There was frank necrosis in the seminiferous tubules in intra-epididymal and thigh region inoculations. The degenerative changes were milder following inoculation in the neck. The germinal epithelium including Sertoli cells and spermatogenic series cells were found susceptible and the seminiferous tubules were often atrophied and hypocellular. The Leydig cells in the interstitium were found more prominent and numerous in animals showing moderate to severe changes in the seminiferous tubules. The blood vessels were not found to be primarily affected in these studies conducted at weekly and fortnightly intervals. The epididymis in the subcutaneously inoculated animals and the accessory sex glands in all the groups were unaffected. The changes in the epididymis occurred when cadmium chloride was injected in the gland itself. In female pigs, the ovaries revealed degeneration of granulosa cells. The graffian follicles were few in number as also the corpora lutea but the corpora albicans were numerous. The other genital parts were found unaffected. Histochemically nicotanamide-adenine dinucleotide hydrate-diaphorase often revealed varying levels of activity particularly indicating changes in interstitial cells which often were proliferated. The changes were also remarkable in ovarian follicles in the theca cells. The 3 ÃŸ-hydroxysteroid dehydrogenase activity levels were generally found nonsignificant. The levels of succinic dehydrogenase were either reduced or remained at the original level. Almost similar was the case with glucose-6-phosphate dehydrogenase.